Pulmonary and Meningeal Cryptococcosis after Corticosteroid Therapy for Autoimmune Hepatitis: Coexistence of Cryptococci within Pulmonary Cancer Nodule - Takashi Yuri; Ayako Kimura; Katsuhiko Yoshizawa; Yuko Emoto; Yuichi Kinoshita; Airo Tsubura (Case Reports in Pathology)
A case of autoimmune hepatitis complicated with pulmonary and meningeal cryptococcosis during long-term treatment with corticosteroid is reported. An 84-year-old woman who received long-term corticosteroid therapy (40 mg/day prednisolone for two years) for autoimmune hepatitis developed a headache, slight fever, and anorexia and was diagnosed with cryptococcal meningitis two months prior to hospital admission. Due to deterioration of her condition, the patient was transferred to our university hospital. After admission, a pulmonary nodule 1 cm in diameter was noticed in the patient’s right lower lobe. Cryptococcal meningitis was diagnosed as positive for cryptococcal antigen from both serum and cerebrospinal fluid (CSF) as well as the growth of Cryptococcus neoformans (C. neoformans) in fungal culture. A combination therapy of amphotericin B and flucytosine was started, and the corticosteroid therapy was gradually reduced and finally discontinued. In addition to continuous cryptococcal infection, complications of Pseudomonas aeruginosa and methicillin-resistance Staphylococcus aureus infection caused death after a 2-month hospitalization. Autopsy disclosed encapsulated yeast in the lungs and subarachnoid space characteristic of Cryptococcus. The pulmonary nodule was found to be squamous cell carcinoma coexisting with C. neoformans within and around the cancer cell nests.